The Atlas obscura explorer's guide to inventing the world - Thuras, Dylan; Swanson, Jennifer (Atlas obscura, 2025)
"Here is a STEM-oriented exploration of the world's most interesting technologies, inventions, and scientific discoveries. Drawing from Atlas obscura's deep catalog of tech-related entries, this book will bring readers to fascinating locations all around the world and move them through the progressions and scientific ideas that forge innovation"-- Provided by publisher.